The Significance of Abolishing Foreign Agents Bill in Ensuring Zourabichvili’s Political Survival - Anindyanari, Laksmitha; Rafael, Patrick (Kelompok Studi Mahasiswa Pengkaji Masalah Internasional Unpar, 2024)
The Foreign Agents Bill caused a significant divide between the Georgian government, its civil society, and President Salome Zourabichvili with her European Union (EU) aspirations, due to its controversial nature of alienating the existence of civil society in the country, along with the fact that it is in direct opposition with the twelve point candidacy criteria issued by the EU – thus endangering any future prospects and relations between Georgia and the EU. This paper will analyze the decision-making processes Zourabichvili employed to navigate this considerable challenge to her political survival as a pro-EU leader. Through the lens of poliheuristic theory, this paper explores two critical dimensions encountered in Zourabichvili’s decision-making process – namely the domestic political and strategic dimensions – through an analysis of her political psychology. It highlights the importance of considering national interests during policy formation, as negative reactions can significantly impact a leader’s political survival and the nation’s geopolitical influence. Keywords: Georgia; European Union; Foreign Agents Bill; Poliheuristic Theory; Political Survival